ON THE HISTORY OF THE RELATIONSHIP BETWEEN LITERATURE AND THE PHENOMENON OF SYNAETHESIA (TAMADDUN NURI JURNALI, 2025)
Although there is much theoretical debate in this area, there is a lack of empirically based research. There is a great need for a broad cross-cultural study of Ullman’s cognitive regularities of synesthesia, especially in-depth testing based on large-scale empirical studies. In addition, the cultural characteristics of synesthesia in different languages are still poorly understood.